Causal relationships between alterations in shear stress-related genes and aneurysmal subarachnoid hemorrhage - Xiaoxin Wu; Yuanyuan Dai; Xingyang Niu; Minghao Zhang; Jiaoxing Li; Yi Xie; Wenli Sheng; Fei Ye (Orphanet Journal of Rare Diseases)
Abstract Background Current management of aneurysmal subarachnoid hemorrhage (aSAH) poses significant challenges, with emerging evidence implicating alterations in shear stress (SS) as critical in disease pathogenesis. However, the causal relationships and underlying molecular mechanisms remain elusive. This study aimed to elucidate the causal association of key SS-related genes with aSAH. Methods SS-related genes were curated from the GeneCards database and transcriptomic datasets responsive to SS conditions. Expression quantitative trait loci (eQTLs) associated with these genes were identified as instrumental variables. An integrative analysis of genome-wide association study data for aSAH with eQTLs was conducted using bidirectional two-sample Mendelian randomization (MR) to identify SS-related genes causally linked to aSAH. Additionally, expression levels of identified genes were compared between ruptured and unruptured aneurysm walls. Functional assessments of these genes in vascular endothelial cells were also performed. Results We identified 209 SS-related genes potentially implicated in aSAH pathogenesis. Using 599 eQTLs correlated with these genes as instrumental variables, MR analysis revealed that KCNN4 (OR = 0.83, 95% CI: 0.73–0.94) and UGCG (OR = 1.62, 95% CI: 1.07–2.48) were significantly associated with aSAH. Furthermore, RNA-sequencing data demonstrated elevated expression of KCNN4 and UGCG in ruptured intracranial aneurysms compared to unruptured ones. Functional experiments using siRNA-mediated knockdown in HUVECs showed that siKCNN4 increased cell proliferation and disrupted endothelial barriers, while siUGCG enhanced tube formation ability but reduced migration. Conclusions Our findings suggest a causal relationship between alterations in SS-related genes and aSAH. Specifically, KCNN4 and UGCG emerge as potential biomarkers critical in the disease progression of aSAH. These insights contribute to a better understanding of the molecular basis of aSAH and may guide future therapeutic strategies targeting SS-related pathways.